Time series interpolation and application of its methods in financial analysis - Mackevičius, Jonas; Valkauskas, Romualdas; Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2020)
In the modern market economy conditions, financial information is very significant when evaluating the results of enterprises’ financial status and activity results. General economic, mathematical, heuristic methods are used for this type of analysis. The article analyses application opportunities for one of the mathematical research methods–time series–as well as its research instruments, discusses the place and role of interpolation methods in a financial analysis. The article reveals that interpolation methods which may be used to determined former values of an enterprise’s financial indicators or identify reasons which determined the enterprise’s financial status and activity results are the following: 1) graphic and arithmetic interpolation in a linear equation; 2) geometric interpolation based on the compound percentage formula and 3) interpolation by averaging.